Recursos didácticos y su influencia en el proceso de enseñanza aprendizaje de los estudiantes de educación básica de la unidad educativa (pcei) personas con escolaridad inconclusa los Rios, (cat) Centro De Apoyo Tutorial Vinces” periodo lectivo 2015 -2016 - Villasagua Ruiz, Saúl Amo (2016)
The present research project called: teaching resources and its influence on the process of teaching and learning of the students of basic education of the educational unit "people with unfinished education (PCEI) rivers, support center Tutorial (CAT) Vinces" academic year 2015-2016, is aimed to meet objective: to determine the level of influence that have teaching resources in the teaching-learning process. For the information, it was necessary to implement surveys to managers; teachers and students thus determined the difficulties in the teaching-learning process. The results obtained indicate that the teaching resources are very important in the teaching-learning process is seen by the directors; While teachers manifest by 42%, that the text is the most widely used resource, students demonstrate 80% that the text is the most used resource. It is important to say that teachers in 16% employ audiovisual projections for supporting the teaching-learning process. Given the demand and the current demand of the society is necessary to respond through innovative research, provide the tools necessary to acquire new knowledge, as it is the case of the teaching resources in the process of teaching-learning, in the institution already mentioned, putting this project into consideration and with good intent.